Longitudinal Study of Habituation and Participatory Design for Multi-User Shared Virtual Environments - Ashraf, N.; Anderson, J.; Douther, C.; McKay, I.; Jack, M.; Platt, P. (International Journal of Virtual Reality, 2001)
This paper details the results of a longitudinal study of user habituation, usage and involvement with a shared virtual 3D environment acting as a meeting space. The study involved investigation of the effectiveness of a range of design features which were included to enhance communication, discussion and social interaction among a group of four users of the shared space. The users took part in six sessions over a period of seven weeks. The paper focuses on usage of the shared space and details user involvement in the design process in terms of reactions to avatar personalisation; avatar life signs, gestures and navigation control; the means for identifying who is talking; and symbolic acting by avatars. The results indicate the importance of key features for the design of virtual environments. Participants wanted to identify their own protocols for turn-taking in conversation and they wanted simple gesture control. For example, one-click visual buttons for the selection of gestures were preferred to pulldown menus. It took users five or six sessions to complete the participatory design process at which point they were totally comfortable with the use of the virtual meeting space. Finally, symbolic acting was shown to be a viable addition to the shared space to assist group dynamics.